Identification of formalin content in salted fish in Kedungprahu traditional market - Fattah Mutiara Rovita; Windi Wulandari (University of Darussalam Gontor, 2022)
Background: Salted fish is one of the food ingredients that is often added with formalin to extend the shelf life of the product, although formalin is a preservative that cannot be used in food. Indonesian traditional markets still often sell salted fish with formalin. Objective: This study aims to analyze the formalin content of salted fish in the Kedungprahu Traditional Market. Method: This research method was a descriptive study using qualitative analysis which includes observing physical characteristics, and formalin testing by using the ET Brand Test Kit. The materials used in the research were all types of salted fishes sold in the Kedungprahu traditional market. The samples taken consisted of 7 types of salted fish with a total of 29 salted fishes tested. The sampling technique was carried out by total sampling. Result: The results showed that salted fishes which had physical characteristics indicated that it contained formalin in anchovy as much as 38.8%. Salted fishes that tested positive in a test kit contained 20.7% formalin, while anchovies had the highest formalin content at up to 40%. 33.3% of salted fish contains formalin, based on the suitability between physical characteristics and test kit tests. Conclution: In the Kedungprahu market, some salted fishes containing formalin is still openly available for purchase. as evidenced by the results of observations of physical characteristics and test kits. AbstrakLatar Belakang: Formalin merupakan pengawet yang dilarang digunakan pada makanan. Pasar Kedungprahu menjadi sasaran para produsen ataupun pedagang ikan asin yang menggunakan formalin sebagai bahan tambahan pangan agar barang dagangannya awet dan tahan lama. Masih minimnya pengetahuan pedagang, produsen, dan masyarakat tentang formalin serta dampak negatif bagi kesehatan. Tujuan: Penelitian ini bertujuan untuk menganalisis kandungan formalin pada ikan asin di Pasar kedungprahu. Metode: Metode penelitian ini adalah penelitian deskriptif menggunakan pendekatan analisis kualitatif yang meliputi pengamatan ciri fisik, dan pengujian formalin menggunakan alat Test Kit Merk ET. Bahan yang digunakan dalam penelitian adalah semua jenis ikan asin yang dijual di Pasar Kedungprahu. Sampel yang diambil terdiri dari 7 jenis ikan asin dengan total sampel yang diuji sejumlah 29 ikan asin. Teknik pengambilan sampel dilakukan dengan cara total sampling. Hasil: Hasil penelitian menunjukkan ciri-ciri ikan asin yang berformalin yakni terdapat bercak putih, tekstur yang keras dan kering, serta tidak berbau khas ikan asin dan apak. Dari 29 sampel yang diuji terdapat 6 (20,7%) diantaranya yang teridentifikasi positif mengandung formalin. Kesimpulan: Ikan asin di Pasar Kedungprahu tidak semua aman untuk dikonsumsi karena mengandung formalin dan dapat menyebabkan dampak negatif bagi kesehatan.